Dynamics of in vitro development of azole resistance in Candida tropicalis. (September 2020) - Paul, Saikat; Singh, Shreya; Sharma, Dipti; Chakrabarti, Arunaloke; Rudramurthy, Shivaprakash M.; Ghosh, Anup K.
Highlights: The present study assessed the dynamics of azole resistance in C. tropicalis . Experimentally fluconazole induced resistant isolates were made. Varying degrees of induced resistance and their stability were noticed among the isolates. Four isolates also showed cross resistance to voriconazole, itraconazole and posaconazole. Development of resistance is due to overexpression of different genes without mutations. Abstract: Objectives: Increasing incidence of azole resistance in Candida tropicalis, especially to fluconazole, has been seen in Asian countries including India. Limited knowledge is available on the molecular mechanisms associated with the development of azole resistance in C. tropicalis . The present study examined the dynamics of in vitro azole resistance in C. tropicalis after prolonged treatment with fluconazole. Methods: Nine fluconazole-susceptible isolates of C. tropicalis were used in this study. Fluconazole resistance was induced experimentally in C. tropicalis isolates. The stability of induced resistance and cross-resistance to other azoles was examined. The molecular mechanisms of azole resistance were assessed by measuring the expression and mutation analysis of different genes. Results: Varying degrees of resistance [five with minimum inhibitory concentrations (MICs) ≤32 mg/L and four with MICs ≥128 mg/L] were noticed, and the resistance was developed in 3 months. Of the nine resistant isolates, four induced resistant isolates with MICs ≥128 mg/L presented temporal resistance stability up to 10 subcultures. These four isolates presented cross-resistance to other azoles and also an inducible overexpression of transporters ( CDR1, CDR2, CDR3 and MDR1 ), ergosterol biosynthesis pathway genes ( ERG1, ERG2, ERG3 and ERG11 ), transcription factors ( TAC1 and UPC2 ) and stress-responsive genes ( HSP90 and MKC1 ) was noticed. No mutations were seen in any of the four genes ( ERG1, ERG3, ERG11 and UPC2 ) tested. Conclusions: Candida tropicalis isolates adapt themselves in the presence of continuous drug exposure and switch back to being susceptible in the absence of the drug. The acquisition of resistance in C. tropicalis is mediated by the overexpression of different resistance-related genes without any molecular alterations.